People Change within Three Days: Khurūj and Character Education among Tablighi Followers in Lombok Island - Irpan Irpan (Islamica: Jurnal Studi Keislaman, 2022)
Tablighi Jama’at is a da‘wah movement that seeks to invite Muslims to return to the pure practice of Islam, with the primary goal being to awaken the spiritual spirit in every Muslim, personally and collectively. Since its presence on the Indian mainland a few decades ago, the Tablighi Jama’at has become the world’s most influential global da‘wah movement. Indonesia, the largest Muslim-majority country in the world, is one of the bases of this movement. This article examines how the Tablighi Jama’at wins huge and loyal followers among the Muslim community in Indonesia. This study focus on revealing a character-building model carried out by the movement in Lombok Island, Indonesia, through one of its essential activities called khurūj fī sabīl Allāh. The author has conducted field research and collected data through participant observation, interviews, and documentation. This study finds that the character-building model performed in khurūj consists of four components: literature or teaching materials, practices, a conducive environment, and evaluations through deliberation. This study argues that khurūj can change people’s character in a relatively short time.